Western Materialism and Modernism's Philosophical Sources - Suraiya IT (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
One of materialism's and modernism's most serious flaws is their failure to take a holistic picture of human life. Transcendental ideals are rejected by almost all modernist ideologists. To put it another way, there is no objective, absolute standard for truth. Truth and moral standards, on the other hand, are only relative, with validity restricted to time, location, and situation. Modernists label societies founded on divine revelation as "static" and "petrified." Change is considered a virtue in and of itself, and the sooner things change, the better. The highest virtue of modernity is being current. The primary goal of this article was to investigate features of Western materialism and modernization, as well as the underlying causes at work in the process of materialism and modernization. It begins by studying the nature of materialism and the modernization process through an examination of the core narrative of Western history. The knowledge gathered from this analysis is utilized to create a conceptual framework. The paradigm is then used to investigate the consequences of Western modernity on non-Western countries.